Intercultural Communication in the Life and Mission of Arnold Janssen - Kasmir Nema (P3TK, Sanata Dharma University, 2020)
This study investigates the intercultural communication dimension of the life and mission of Arnold Janssen, the founder of the Divine Word Missionaries (SVD). This qualitative study involves a textual analysis of the relevant data and verbal descriptions of Janssens life and mission. The results of the study show that the seed of Janssens intercultural communication was primarily rooted in his parents. Being born in a family that was enveloped by a culture of prayer and a culture of peace, Janssen cultivated an intercultural sensitivity. This seed sprouted in his personality and spirituality. It revealed that Janssen was an intercultural-and-receptive person, interested in ethnic groups, cultures, beliefs, and nationalities which were different from his own. Such interests were founded by a venturesome spirit that allowed him to welcome the unfamiliarity of the other and to value such differences. The researcher finds that Janssens intercultural communication was contained in his practice of mission as dialogue. Through the lenses of the mission, Janssens dialogue competence enabled him to bridge differing views about the mission and encourage missionaries to do the same.